Changes in the Rate of Profit and Switches of Techniques - Pasinetti, Luigi L. (Quarterly Journal of Economics, 1966)
I. A numerical example, 504. â€” II. Generalizations, 508. â€” III. A direct logical criticism, 510. â€” IV. Changes in the rate of profit and changes in the â€œquantity of capital, â€ 512. â€” V. The trap of an old mode of thinking, 514.